Soft capsule wall material with anti-aging and anti-leakage functions and preparation method of soft capsule wall material

By using a combined matrix of gelatin, succinic anhydride and sodium carboxymethylcellulose, the problems of aging and leakage of soft capsule capsules are solved, and a capsule with high stability and good application prospects are achieved.

CN119656128APending Publication Date: 2025-03-21LIAONING UNIV OF TRADITIONAL CHINESE MEDICINE
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411886624.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

Soft capsule capsules are prone to aging, adhesion and leakage during storage, which affects their stability.

Method used

Gelatin, succinic anhydride and sodium carboxymethylcellulose are used as a combination matrix of the capsule material, and formed through acylation reaction and hydrogen bonding to improve the anti-aging and leakage properties of the capsule material.

Benefits of technology

The soft capsule capsule material is anti-aging and leak-proof, improving its stability and application prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119656128A_ABST
    Figure CN119656128A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of medicinal materials, and particularly relates to an anti-aging and anti-leakage soft capsule wall material and a preparation method thereof. The soft capsule wall material comprises the following raw materials in percentage by mass: 10%-15% of gelatin, 0.4%-2% of succinic anhydride, 4%-6% of glycerol, 0.08%-0.13% of sodium carboxymethyl cellulose and 78%-85% of purified water. The capsule material provided by the invention can simultaneously solve the problem of slow disintegration caused by an oxidation cross-linking reaction and the problem of leakage caused by strong hygroscopicity in the storage process, is simple in production process and high in safety, and has a very good application prospect in the field of soft capsule preparations.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of medicinal materials, and specifically relates to a soft capsule material having both anti-aging and anti-leakage properties and a preparation method thereof. Background Art

[0002] Soft capsules refer to capsules that are directly encapsulated with a certain amount of liquid raw materials, or solid raw materials dissolved or dispersed in appropriate excipients to prepare solutions, suspensions, emulsions or semi-solids, and then sealed in soft capsule materials. Because of their high bioavailability, ability to mask the bad smell of drugs and improve drug stability, they are widely used in the fields of pharmaceuticals, food and chemicals.

[0003] Most soft capsule materials are gelatin, which is a protein containing 18 kinds of amino acids degraded from animal skin, bones or connective tissue. Because gelatin has the advantages of good film-forming properties, low cost and degradability, it has attracted much attention from researchers. In recent years, the shortcomings of gelatin-based soft capsule materials have also become obvious during their use. During storage, soft capsules will have problems such as shell aging, adhesion and even leakage that affect stability. The occurrence of aging problems is related to the cross-linking reaction. The occurrence of the cross-linking reaction is affected by many factors. Its mechanism is that the aldehyde group reacts with the free amino group in the gelatin molecule to form a Schiff base reaction, forming an insoluble film on the surface of the gelatin, resulting in slow disintegration; and the adhesion and leakage of the capsule shell are attributed to the fact that the glycerol and gelatin itself in the capsule shell contain a large number of hydrophilic groups, resulting in strong hygroscopicity inducing water to enter the capsule shell, and eventually leakage occurs, thereby affecting the stability of the soft capsule material.

[0004] Therefore, how to solve the two problems of aging and leakage at the same time is a difficult problem in the development and application of soft capsule materials. Summary of the invention

[0005] In view of the above technical problems, the present invention provides a soft capsule material having both anti-aging and anti-leakage properties and a preparation method thereof. The present invention can solve the aging and leakage problems of the soft capsule material at the same time.

[0006] In order to achieve the above object, the present invention provides the following technical solutions.

[0007] A soft capsule material with both anti-aging and anti-leakage properties comprises the following raw materials in percentage by mass: 10%-15% gelatin, 0.4%-2% succinic anhydride, 4%-6% glycerol, 0.08%-0.13% sodium carboxymethyl cellulose and 78%-85% purified water.

[0008] Furthermore, the gelatin is a hide glue and bone glue with a mass ratio of 1:1.

[0009] A method for preparing a soft capsule material having both anti-aging and anti-leakage properties, comprising the following steps: Step 1, mixing gelatin, glycerin and part of water, heating and stirring to react until a uniform liquid is formed to obtain gelatin solution; Step 2, adding succinic anhydride into gelatin solution, heating and stirring to react, to obtain succinylated gelatin solution; Step 3, dissolving sodium carboxymethyl cellulose in the remaining water under heating and stirring to form a transparent and clear liquid to obtain a sodium carboxymethyl cellulose solution; Step 4, heating and mixing the succinylated gelatin solution and the sodium carboxymethyl cellulose solution for 1 hour to obtain a mixed solution; Step 5: Transfer the mixed solution to a film-forming container for film-forming and drying. After drying, peel off the film to obtain the soft capsule material.

[0010] Furthermore, in steps 1, 2, 3 and 4, the heating temperature is 45°C.

[0011] Furthermore, in steps 1, 2, 3 and 4, the stirring speed is 160 rpm.

[0012] Furthermore, in step 2, the reaction time is 1 hour, and the pH is 9 during the reaction; after the reaction is completed, the pH is adjusted to 6.

[0013] Furthermore, during the reaction, the pH value was adjusted with a 1 mol / L sodium hydroxide solution, and after the reaction, the pH value was adjusted with a 1 mol / L hydrochloric acid solution.

[0014] Furthermore, in step 5, the drying temperature is 40° C. and the drying time is 16-20 h.

[0015] Compared with the prior art, the beneficial effects of the present invention are as follows.

[0016] The soft capsule material provided by the invention has low cost, high safety and simple preparation method; succinylated gelatin and sodium carboxymethyl cellulose are used as the combined matrix of the soft capsule material, which has the advantages of fast disintegration time and reduced hygroscopicity, and has good application prospects in the field of soft capsule preparations. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 The puncture load variation curves of Examples 1-3 and Comparative Examples 1-4 under 40°C saturated NaCl environment over time.

[0018] Figure 2 Appearance comparison diagram of Examples 1-3 and Comparative Examples 1-4.

[0019] Figure 3 Infrared spectra of Comparative Example 1, Comparative Example 2 and Example 2 and their physical mixtures.

[0020] Figure 4 X-ray diffraction patterns of Example 2 and Comparative Example 1, Comparative Example 2 and physical mixtures thereof.

[0021] Figure 5 DSC graphs of Comparative Example 1, Comparative Example 2 and Example 2 and their physical mixtures.

[0022] Figure 6 Microscopic morphology images of Comparative Example 1, Comparative Example 2 and Example 2. DETAILED DESCRIPTION

[0023] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0024] Unless otherwise defined, all technical and scientific terms used in the present invention have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention.

[0025] Example 1.

[0026] The soft capsule material with both anti-aging and anti-leakage properties includes the following raw materials: Gelatin 20 g (hide glue: 10 g; bone glue: 10 g); glycerol 6.4 g; succinic anhydride 1.8 g; sodium carboxymethyl cellulose 0.15 g; purified water 110 g.

[0027] The method for preparing a soft capsule material having both anti-aging and anti-leakage properties comprises the following steps: Step 1. Accurately weigh 20.00 g of gelatin (hide glue: bone glue = 1:1) and 6.4 g of glycerin into a beaker, add 95 ml of purified water, stir and dissolve at 45 °C, stirring at a rate of 160 rpm for 1 h to form a uniform liquid to obtain gelatin solution; Step 2, then gradually add 1.8 g of succinic anhydride to the gelatin solution under stirring, continue stirring at 45°C and 160 rpm for 1 h, and simultaneously maintain the pH of the reaction system at 9 with 1 mol / L sodium hydroxide solution, and after the two are completely reacted, adjust the pH of the gelatin solution to 6 with 1 mol / L hydrochloric acid solution to obtain succinylated gelatin gelatin solution; Step 3, accurately weigh 0.15 g of sodium carboxymethyl cellulose solution, add 15 ml of purified water, and stir at 45° C. and 160 rpm to form a transparent and clear liquid to obtain a sodium carboxymethyl cellulose solution; Step 4, mixing and stirring the succinylated gelatin solution and the sodium carboxymethyl cellulose solution at 45° C. and 160 rpm for 1 hour to obtain a mixed solution; Step 5: Pour the mixed solution into a culture dish while it is still hot, cool it to room temperature, and dry it with air at 40°C for 16 hours. After drying, peel it off to obtain soft capsule material.

[0028] Example 2.

[0029] The soft capsule material with both anti-aging and anti-leakage properties includes the following raw materials: Gelatin 20 g (hide glue: 10 g; bone glue: 10 g); glycerol 7 g; succinic anhydride 0.6 g; sodium carboxymethyl cellulose 0.16 g; purified water 110 g.

[0030] The method for preparing a soft capsule material having both anti-aging and anti-leakage properties comprises the following steps: Step 1. Accurately weigh 20.00 g of gelatin (hide glue: bone glue = 1:1) and 7 g of glycerin into a beaker, add 95 ml of purified water, stir and dissolve at 45°C, stirring at a rate of 160 rpm for 1 h to form a uniform liquid to obtain gelatin solution; Step 2, then gradually add 0.6 g of succinic anhydride to the gelatin solution under stirring, continue stirring at 45°C and 160 rpm for 1 h, and simultaneously maintain the pH of the reaction system at 9 with 1 mol / L sodium hydroxide solution, and after the two are completely reacted, adjust the pH of the gelatin solution to 6 with 1 mol / L hydrochloric acid solution to obtain succinylated gelatin gelatin solution; Step 3, accurately weigh 0.16 g of sodium carboxymethyl cellulose solution, add 15 ml of purified water, and stir at 45° C. and 160 rpm to form a transparent and clear liquid to obtain a sodium carboxymethyl cellulose solution; Step 4, mixing and stirring the succinylated gelatin solution and the sodium carboxymethyl cellulose solution at 45° C. and 160 rpm for 1 hour to obtain a mixed solution; Step 5: Pour the mixed solution into a culture dish while it is still hot, cool it to room temperature, and dry it with air at 40°C for 16 hours. After drying, peel it off to obtain soft capsule material.

[0031] Example 3.

[0032] The soft capsule material with both anti-aging and anti-leakage properties includes the following raw materials: Gelatin 20 g (hide glue: 10 g; bone glue: 10 g); glycerol 7.4 g; succinic anhydride 1 g; sodium carboxymethyl cellulose 0.18 g; purified water 110 g.

[0033] The method for preparing a soft capsule material having both anti-aging and anti-leakage properties comprises the following steps: Step 1. Accurately weigh 20.00 g of gelatin (hide glue: bone glue = 1:1) and 7.4 g of glycerin into a beaker, add 95 ml of purified water, stir and dissolve at 45 °C, stirring at a rate of 160 rpm for 1 h to form a uniform liquid to obtain gelatin solution; Step 2, then gradually add 1 g of succinic anhydride to the gelatin solution under stirring, continue stirring at 45°C and 160 rpm for 1 h, and simultaneously maintain the pH of the reaction system at 9 with 1 mol / L sodium hydroxide solution, wait for the two to react completely, and adjust the pH of the gelatin solution to 6 with 1 mol / L hydrochloric acid solution to obtain succinylated gelatin gelatin solution; Step 3, accurately weigh 0.18 g of sodium carboxymethyl cellulose solution, add 15 ml of purified water, and stir at 45° C. and 160 rpm to form a transparent and clear liquid to obtain a sodium carboxymethyl cellulose solution; Step 4, mixing and stirring the succinylated gelatin solution and the sodium carboxymethyl cellulose solution at 45° C. and 160 rpm for 1 hour to obtain a mixed solution; Step 5: Pour the mixed solution into a culture dish while it is still hot, cool it to room temperature, and dry it with air at 40°C for 16 hours. After drying, peel it off to obtain soft capsule material.

[0034] Comparative example 1.

[0035] Conventional soft capsule material formula: Gelatin 20 g (hide glue: 10 g; bone glue: 10 g); glycerin 10.4 g; purified water 110 g.

[0036] Preparation steps: Accurately weigh 20.00 g of gelatin (hide glue: bone glue = 1:1) and place it in a 500 ml beaker, add 7 g of glycerol and 110 ml of pure water, stir to dissolve at 45°C, stirring at 160 rpm for 1 h; pour into a culture dish while hot, cool to room temperature; dry with air at 40°C to obtain commercially available conventional gelatin film.

[0037] Comparative example 2.

[0038] Acylated Ming capsule material formula: Gelatin 20 g (hide glue: 10 g; bone glue: 10 g); glycerol 7 g; succinic anhydride 0.6 g; purified water 110 g.

[0039] Preparation steps of acylated alum capsule material: Step 1. Accurately weigh 20.00 g of gelatin (hide glue: bone glue = 1:1) and 7 g of glycerin into a beaker, add 110 ml of purified water, stir and dissolve at 45°C, stirring at 160 rpm for 1 h to form a uniform liquid to obtain gelatin solution; Step 2, then gradually add 0.6 g of succinic anhydride to the gelatin solution under stirring, continue stirring at 45°C and 160 rpm for 1 h, and simultaneously maintain the pH of the reaction system at 9 with 1 mol / L sodium hydroxide solution, and after the two are completely reacted, adjust the pH of the gelatin solution to 6 with 1 mol / L hydrochloric acid solution to obtain succinylated gelatin gelatin solution; Step 3: Pour the succinylated gelatin solution into a culture dish while it is still hot, cool it to room temperature, and dry it with air at 40°C for 16 hours. After drying, peel it off to obtain acylated gelatin capsule material.

[0040] Comparative example 3.

[0041] Soft capsule materials include the following raw materials: Gelatin 20 g (hide glue: 10 g; bone glue: 10 g); glycerol 8 g; succinic anhydride 0.2 g; sodium carboxymethyl cellulose 0.1 g; purified water 110 g.

[0042] Soft capsule material preparation steps: Step 1. Accurately weigh 20.00 g of gelatin (hide glue: bone glue = 1:1) and 8 g of glycerin into a beaker, add 95 ml of purified water, stir and dissolve at 45°C at a stirring rate of 160 rpm for 1 h to form a uniform liquid to obtain gelatin solution; Step 2, then gradually add 0.2 g of succinic anhydride to the gelatin solution under stirring, continue stirring at 45°C and 160 rpm for 1 h, and simultaneously maintain the pH of the reaction system at 9 with 1 mol / L sodium hydroxide solution, wait for the two to react completely, and adjust the pH of the gelatin solution to 6 with 1 mol / L hydrochloric acid solution to obtain succinylated gelatin gelatin solution; Step 3, accurately weigh 0.1 g of sodium carboxymethyl cellulose solution, add 15 ml of purified water, and stir at 45° C. and 160 rpm to form a transparent and clear liquid to obtain a sodium carboxymethyl cellulose solution; Step 4, mixing and stirring the succinylated gelatin solution and the sodium carboxymethyl cellulose solution at 45° C. and 160 rpm for 1 hour to obtain a mixed solution; Step 5: Pour the mixed solution into a culture dish while it is still hot, cool it to room temperature, and dry it with air at 40°C for 16 hours. After drying, peel it off to obtain soft capsule material.

[0043] Comparative example 4.

[0044] Soft capsule materials include the following raw materials: Gelatin 20 g (hide glue: 10 g; bone glue: 10 g); glycerol 5 g; succinic anhydride 0.6 g; sodium carboxymethyl cellulose 2 g; purified water 110 g.

[0045] Soft capsule material preparation steps: Step 1. Accurately weigh 20.00 g of gelatin (hide glue: bone glue = 1:1) and 5 g of glycerin into a beaker, add 95 ml of purified water, stir and dissolve at 45°C at a stirring rate of 160 rpm for 1 h to form a uniform liquid to obtain gelatin solution; Step 2, then gradually add 0.6 g of succinic anhydride to the gelatin solution under stirring, continue stirring at 45°C and 160 rpm for 1 h, and simultaneously maintain the pH of the reaction system at 9 with 1 mol / L sodium hydroxide solution, and after the two are completely reacted, adjust the pH of the gelatin solution to 6 with 1 mol / L hydrochloric acid solution to obtain succinylated gelatin gelatin solution; Step 3, accurately weigh 2 g of sodium carboxymethyl cellulose solution, add 15 ml of purified water, and stir at 45°C and 160 rpm to form a transparent and clear liquid to obtain a sodium carboxymethyl cellulose solution; Step 4, mixing and stirring the succinylated gelatin solution and the sodium carboxymethyl cellulose solution at 45° C. and 160 rpm for 1 hour to obtain a mixed solution; Step 5: Pour the mixed solution into a culture dish while it is still hot, cool it to room temperature, and dry it with air at 40°C for 16 hours. After drying, peel it off to obtain soft capsule material.

[0046] test: A formaldehyde solution with a concentration of 44.4 mg / ml was prepared as a fumigation environment, and the soft capsule material samples prepared in Examples 1-3 and Comparative Examples 1-4 were cut into films with a size of 20 mm×15 mm×0.50 mm, placed in formaldehyde vapor for 45 minutes, and then taken out. The disintegration time was investigated with reference to the disintegration time limit inspection method item 0921 of Part IV of the 2020 edition of the Chinese Pharmacopoeia, as shown in Table 1.

[0047] Table 1 Comparison of disintegration time of Examples 1-3 and Comparative Examples 1-4 under formaldehyde fumigation conditions.

[0048] The data in Table 1 above show that: in Comparative Examples 1 and 3, the succinic anhydride was not modified or the modifier was less, resulting in no significant shortening of the disintegration time, which indicates that the aging problem has not been well solved; while the soft capsule materials of Examples 1, 2, and 3 of the present invention all have good anti-aging effects.

[0049] The soft capsule material samples prepared in Examples 1-3 and Comparative Examples 1-2 were cut into films of sizes of 15 mm×15 mm×0.50 mm and 50 mm×3 mm×0.50 mm, and the puncture load and Young's modulus were measured at a rate of 1.5 mm / s under a texture analyzer to investigate their mechanical properties, as shown in Table 2.

[0050] Table 2 Comparison of mechanical properties of Comparative Examples 1, 2 and Example 1.

[0051] The data in Table 2 above show that: in Comparative Example 4, the puncture load and the Young's modulus are too large, and the prepared capsule shell is relatively hard; in Comparative Example 3, the capsule shell is relatively soft, and the puncture load and the Young's modulus are relatively small, which are not conducive to storage, while the soft capsule materials of Examples 1-3 of the present invention have good mechanical properties.

[0052] The soft capsule material samples prepared in Examples 1-3 and Comparative Examples 1-4 were cut into a size of 15 mm×15 mm×0.50 mm and placed in a saturated NaCl environment at 40°C for 0, 0.5, 1, 1.5, 2, 3, 4, 6, 8, 10, 12, 16, 20, 24, 32, and 48 h, and taken out every 12 h after 48 h. The puncture load was measured under a texture analyzer, and a nonlinear curve was fitted according to its change trend. A tangent was drawn to the curve, and the abscissa of the intersection of the tangents was the storage time. Figure 1 shown.

[0053] Table 3 Comparison of storage time of Examples 1-3 and Comparative Examples 1-4.

[0054] According to the data in Table 3, it can be seen that: According to the curve change trend, it can be seen that as time goes by, moisture enters the system, resulting in a decrease in the mechanical properties of the capsule material, and finally reaching a balance. The storage time of comparative examples 1-3 in the present invention is short, which is not conducive to production; while the storage time of examples 1-3 in a hot and humid environment is long, which shows that the capsule material formula in this example has a certain effect of preventing capsule shell leakage. The appearance of examples 1-3 of the present invention and comparative examples 1-4 are compared, as shown in FIG. Figure 2 shown.

[0055] pass Figure 2 It can be seen that there is no obvious difference in appearance between the capsule materials prepared in Examples 1-3 and the comparative example.

[0056] Take Example 2 as an example, and compare it with Comparative Examples 1 and 2 to characterize its structure and properties. Dry the water of Comparative Example 1, Comparative Example 2, Example 2, the physical mixture of Comparative Example 1 and succinic anhydride, the physical mixture of Comparative Example 1 and succinic anhydride and sodium carboxymethyl cellulose, and the physical mixture of Comparative Example 2 and sodium carboxymethyl cellulose at 105°C and grind into powder. Mix with potassium bromide KBr powder and press into tablets for infrared spectroscopy analysis. Test conditions: wavelength range 4000-400 cm -1 , scanned 32 times, with a resolution of 4 cm -1 ,like Figure 3 As shown. (Comparative Example 1 and physical mixture of succinic anhydride: grind the sample of Comparative Example 1 into powder and mix it with the powder of succinic anhydride in a ratio of 1:1; the preparation steps of the physical mixture of Comparative Example 2 and sodium carboxymethyl cellulose are the same; Comparative Example 1 and physical mixture of succinic anhydride and sodium carboxymethyl cellulose: grind the samples of Comparative Example 1, succinic anhydride and sodium carboxymethyl cellulose into powder and mix them in a ratio of 1:1:1).

[0057] Figure 3 The curve shows that the gelatinamide A band is at 3400 cm -1 There is an absorption peak at 2900 cm-1, which is the absorption peak of NH or OH stretching vibration. Due to the existence of hydrogen bonds within and between gelatin molecules, the peak is broad. -1 The weak absorptions on the left and right are caused by the CN stretching vibration of the amide B band; at 1630 cm -1 The absorption peak near is the characteristic band of carbonyl C=O stretching vibration in amide I band; amide II band is located at 1540 cm -1 The absorption peak near the center is mainly caused by the strong coupling between gelatin C-stretching vibration and NH bending vibration; the amide III band is located at 1200 cm -1 It is mainly caused by the CN stretching vibration and NH plane bending vibration of gelatin; the characteristic absorption peak of gelatin can be observed in all six samples.

[0058] Compared with Comparative Example 1, the spectrum of acylated gelatin in Comparative Example 2 shows that the acylated gelatin has a peak at 1590 cm -1 The sum of 1200cm -1 The absorption peaks of amide II and III bands nearby are enhanced, which proves the formation of amide bond; in addition, the phenomenon that amide A band and Ⅰ band move to high wave number direction also proves the occurrence of acylation reaction; compared with the infrared spectrum of the physical mixture of comparative example 1 and succinic anhydride, it can be found that the absorption peak at 904 cm in the physical mixture -1 There is a characteristic peak of stretching vibration of COC bond unique to succinic anhydride, but this peak is not observed in the spectrum of acylated gelatin film, which shows that gelatin and succinic anhydride are not just a simple physical mixture.

[0059] From the spectrum of Example 2, it can be observed that some peaks are shifted to new frequencies before and after the addition of sodium carboxymethyl cellulose. The absorption peak corresponding to the amide A band in the spectrum of acylated gelatin appears at 3408 cm -1 However, in the spectrum of the capsule material prepared in Example 2, it moves to a lower wave number, at 3380 cm -1 The amide I band corresponding to 1632 cm -1 After adding sodium carboxymethyl cellulose, the wave number shifted to 1630 cm -1 ; 1597 cm in acylated gelatin film -1 After adding sodium carboxymethyl cellulose, the wave number shifted to 1600 cm -1 , significantly reducing the NH absorption peak intensity; the 1199 cm -1 The absorption peak shifted to 1120 cm -1 The change in the spectrum proves that the conformational change has occurred in the gelatin molecule. In addition, the peak type of the amide A band has become wider, which more strongly confirms that the sodium carboxymethyl cellulose and the gelatin molecules have produced intermolecular hydrogen bonds, resulting in an increase in NH or OH chemical bonds in the system. At the same time, no movement of the absorption peak wavenumber was found in the spectrum of the physical mixture of comparative example 2 and sodium carboxymethyl cellulose, and the absorption peak intensity of the amide A band did not increase, which shows that simple physical powder mixing does not lead to an increase in hydrogen bonds between sodium carboxymethyl cellulose and gelatin.

[0060] It can be seen from the infrared spectrum that an acylation reaction occurs between succinic anhydride and gelatin, and the free amino groups in the gelatin molecules are reduced. This explains why the disintegration time of Examples 1, 2, 3 and Comparative Example 2 after formaldehyde vapor treatment is shorter than that of Comparative Example 1. The addition of sodium carboxymethyl cellulose forms intermolecular hydrogen bonds with -OH or -NH groups in the acylated gelatin, reducing the exposure of hydrophilic groups. This is the fundamental reason why the capsule shell material is leak-proof.

[0061] The physical mixture of Comparative Example 1, Comparative Example 2, Example 2, Comparative Example 1 and succinic anhydride, the physical mixture of Comparative Example 1 and succinic anhydride and sodium carboxymethyl cellulose, and the physical mixture of Comparative Example 2 and sodium carboxymethyl cellulose were dried and ground into powder. The XRD patterns of the samples were measured by X-ray diffractometer. The 2θ scanning range was 5° to 80°, and the speed was 2° / min. The data were analyzed as follows: Figure 4 shown.

[0062] Figure 4The curve shows that there is a small peak at 2θ=7°-8° in the curve of Comparative Example 1, which is attributed to the triple helical structure in gelatin, but the peak intensity is weakened in Comparative Example 2, indicating that its triple helical structure is destroyed, which is related to the acylation reaction between the amino group in gelatin and the acid anhydride. The curve has a broad diffraction peak at 2θ=19.8°, which usually represents the left-handed helical structure of gelatin molecules and belongs to the amorphous structure of gelatin. In the system of Example 2, after the addition of sodium carboxymethyl cellulose, the intensity of the diffraction peak at this location is weakened. This is because sodium carboxymethyl cellulose and gelatin molecules produce intermolecular hydrogen bonds, destroying the regular structure of gelatin, thereby reducing the crystallinity, confirming the conclusion of infrared spectroscopy. From the curves of Comparative Example 1, the physical mixture of succinic anhydride and sodium carboxymethyl cellulose, and the physical mixture of Comparative Example 1 and succinic anhydride and Comparative Example 2, it can be seen that succinic anhydride has a diffraction peak in the physical mixture, but it is not observed in Comparative Example 2, which shows that succinic anhydride exists in an amorphous form in Comparative Example 2. The physical mixture curve of Comparative Example 2 and sodium carboxymethyl cellulose is substantially consistent with the curve of Comparative Example 2, which indicates that sodium carboxymethyl cellulose itself is an amorphous structure.

[0063] Comparative Example 1, Comparative Example 2, Example 2, a physical mixture of Comparative Example 1 and succinic anhydride, a physical mixture of Comparative Example 1 and succinic anhydride and sodium carboxymethyl cellulose, and a physical mixture of Comparative Example 2 and sodium carboxymethyl cellulose were placed in crucibles, heated at a heating rate of 10°C / min in a temperature range of 10-380°C, and continuously purged with nitrogen at a flow rate of 20 mL / min, as shown in FIG. Figure 5 shown.

[0064] From the DSC curves of Comparative Example 1, Comparative Example 2 and Example 2, two obvious endothermic peaks can be seen. The first endothermic peak is near 100°C, which is caused by the evaporation of water near 100°C, and the other endothermic peak appears at about 250°C, which is caused by the melting of the film itself. Through data analysis, it can be seen that the Tg of Comparative Example 1 is 70.14°C and the melting point is 260.67°C; the Tg of Comparative Example 2 is 72.15°C and the melting point is 257.67°C; the Tg of Example 2 is 77.36°C and the melting point is 273.00°C; the addition of sodium carboxymethyl cellulose leads to an increase in the glass transition temperature and melting point in the system, proving that the thermal stability of the capsule material in Example 2 is improved. In Example 2, there is only one glass transition temperature, but compared with the curves of the three physical mixtures, there is not only one glass transition temperature, which shows that the compatibility between sodium carboxymethyl cellulose and gelatin is good.

[0065] In the physical mixture diagram of succinic anhydride, the endothermic peak generated by the melting of anhydride at 118°C can be clearly seen, but this peak is not observed in Comparative Example 2, proving that succinic anhydride does not exist as a separate structure in Comparative Example 2, which is consistent with the conclusions of the infrared spectrum and X-ray diffraction diagram.

[0066] It can be seen from the DSC curve that the capsule material formula of Example 2 of the present invention has better thermal stability than the conventional gelatin formula in Comparative Example 1.

[0067] The samples of Comparative Example 1, Comparative Example 2 and Example 2 were subjected to gold spraying treatment and then the microscopic morphology of the surface was observed at a magnification of 2000 x and the cross section at a magnification of 10000 x using a scanning electron microscope. Figure 6 shown.

[0068] Figure 6 In the figure, the apparent difference between Comparative Example 1 and Comparative Example 2 is not significant, but the cross-sectional morphology shows that the addition of succinic anhydride makes the structure rougher, proving the occurrence of chemical reaction, which is consistent with the infrared spectrum results. The apparent difference between Comparative Example 2 and Example 2 is not obvious, which shows that the addition of sodium carboxymethyl cellulose does not affect the apparent morphology of the composite film, proving that gelatin and sodium carboxymethyl cellulose have good compatibility; by comparing the cross-sectional morphology, the cross-sectional morphology of Comparative Example 2 is rough and honeycomb-like, but the cross-sectional morphology of Example 2 is smoother and more uniform than that of Comparative Example 2, because the sodium carboxymethyl cellulose forms hydrogen bonds with the modified gelatin, thereby improving the density of the internal structure.

[0069] The above embodiments are intended to illustrate the present invention rather than to limit the present invention. Any simple transformation, equivalent replacement, or improvement of the solutions of the present invention should be included in the protection scope of the present invention.

Claims

1. A soft capsule material having both anti-aging and anti-leakage properties, characterized in that: The invention comprises the following raw materials in percentage by mass: 10% to 15% gelatin, 0.4% to 2% succinic anhydride, 4% to 6% glycerol, 0.08% to 0.13% sodium carboxymethyl cellulose and 78% to 85% purified water.

2. The soft capsule material having both anti-aging and anti-leakage properties according to claim 1, characterized in that: The gelatin is prepared in a hide glue to bone glue mass ratio of 1:

1.

3. A method for preparing a soft capsule material having both anti-aging and anti-leakage properties, characterized in that: The steps include: Step 1, mixing gelatin, glycerin and part of water, heating and stirring to react until a uniform liquid is formed to obtain gelatin solution; Step 2, adding succinic anhydride into gelatin solution, heating and stirring to react, to obtain succinylated gelatin solution; Step 3, dissolving sodium carboxymethyl cellulose in the remaining water under heating and stirring to form a transparent and clear liquid to obtain a sodium carboxymethyl cellulose solution; Step 4, heating and mixing the succinylated gelatin solution and the sodium carboxymethyl cellulose solution for 1 hour to obtain a mixed solution; Step 5: Transfer the mixed solution to a film-forming container for film-forming and drying. After drying, peel off the film to obtain the soft capsule material.

4. The method for preparing the soft capsule material having both anti-aging and anti-leakage properties according to claim 3, characterized in that: In the steps 1, 2, 3 and 4, the heating temperature is 45°C.

5. The method for preparing the soft capsule material having both anti-aging and anti-leakage properties according to claim 3, characterized in that: In steps 1, 2, 3 and 4, the stirring speed is 160 rpm.

6. The method for preparing the soft capsule material having both anti-aging and anti-leakage properties according to claim 3, characterized in that: In step 2, the reaction time is 1 hour, and the pH value during the reaction is 9; after the reaction is completed, the pH value is adjusted to 6.

7. The method for preparing the soft capsule material having both anti-aging and anti-leakage properties according to claim 3, characterized in that: During the reaction, the pH value was adjusted with a 1 mol / L sodium hydroxide solution, and after the reaction, the pH value was adjusted with a 1 mol / L hydrochloric acid solution.

8. The method for preparing the soft capsule material having both anti-aging and anti-leakage properties according to claim 3, characterized in that: In step 5, the drying temperature is 40° C. and the drying time is 16-20 h.

Citation Information

Cited By

  • Ethyl eicosapentaenoate soft capsule and preparation process thereof

    CN120643526A